Subjective and objective refractions in eyes with extended‐depth‐of‐focus intraocular lenses using echelette optics: clinical and experimental study. Issue 6 (16th November 2020) - Ota, Yuka; Minami, Keiichiro; Oki, Shinichi; Bissen‐Miyajima, Hiroko; Okamoto, Keiichiro; Nakashima, Masaya; Tsubota, Kazuo
Abstract: Purpose: To evaluate differences in subjective and objective refractions in eyes with extended‐depth‐of‐focus intraocular lenses (EDOF IOLs) using echelette optics, and the effect of the light wavelength used during examinations. Methods: In the prospective study, subjective and objective refractions of 128 eyes of 64 patients were examined 3 months after implantation of the EDOF IOLs (ZXR00V, Johnson & Johnson Surgival Vision). Objective refractions were measured using an autorefractor with a near‐infrared (NIR) light source. Clinical differences in the spherical, cylindrical and spherical equivalent (SE) refractions between the subjective and objective refractions were evaluated. Then, lens powers of monofocal, EDOF and diffractive bifocal IOLs in the use of a 850‐nm light source were measured experimentally for using a lensmeter, and the differences from the monofocal IOLs were calculated. Results: The mean objective refractions were more myopic (p < 0.001) than the subjective refractions; the differences in the spherical, cylindrical and SE refractions were −0.71, −0.26 and −0.84 dioptre, respectively. Experimental investigation resulted that there was the mean difference of 0.83 D with the EDOF from monofocal IOLs at 850 nm, while the difference was −0.20 D with bifocal IOLs. Conclusions: The diffractive EDOF IOLs using echelette gratings inherently induced constant differences in the subjective and objective refractions, which arose from the chromatic difference in IOL powers for the visible and NIR lights.